A meta-analysis investigating the relationship between inflammation in autoimmune disease, elevated CRP, and the risk of dementia - Cooper, Joseph; Pastorello, Ylenia; Slevin, Mark (Frontiers in Immunology, 2023)
Alzheimer’s Disease (AD) represents the most common type of dementia and is becoming a steadily increasing challenge for health systems globally. Inflammation is developing as the main focus of research into Alzheimer’s disease and has been demonstrated to be a major driver of the pathologies associated with AD. This evidence introduces an interesting research question, whether chronic inflammation due to pathologies such as inflammatory bowel disease (IBD) and rheumatoid arthritis (RA) could lead to a higher risk of developing dementia. In both IBD and RA, increased levels of the inflammatory biomarker C-reactive protein (CRP) can be highlighted, the latter being directly implicated in neuroinflammation and AD. In this meta-analysis both the association between chronic inflammatory diseases and elevated levels of CRP during midlife were investigated to examine if they correlated with an augmented risk of dementia. Moreover, the association between increased CRP and modifications in the permeability of the Blood Brain Barrier (BBB) in the presence of CRP is explored. The results displayed that the odds ratio for IBD and dementia was 1.91 [1.15-3.15], for RA it was 1.90 [1.09-3.32] following sensitivity analysis and for CRP it was 1.62 [1.22-2.15]. These results demonstrate a higher risk of dementia in patients presenting chronic inflammation and that exists an independent association with high CRP in midlife. This paper builds on published research that suggest a critical role for CRP both in stroke and AD and provides an analysis on currently published research on multiple diseases (IBD and RA) in which CRP is raised as well as chronically elevated. CRP and the associated risk of dementia and further research indicated that the monomeric form of CRP can infiltrate the BBB/be released from damaged micro-vessels to access the brain. This meta-analysis provides first-time evidence that chronic elevation of CRP in autoimmune diseases is directly associated to an increased risk of later development of Alzheimer’s disease. Therefore, greater priority should be provided to the effective control of inflammation in patients with chronic inflammatory or autoimmune conditions and further long-term assessment of circulating CRP might inform of an individual’s relative risk of developing dementia.